Uloga i razvoj metapodataka u opisivanju mrežnih izvora informacija - Vrana, Radovan (1998)
Human knowledge is stored in different ways in order to be preserved for the future generations. To enable an adequate approach to knowledge, to enable the users themselves to efficiently find their information subject cataloguing is more than necessary. One of the ways of documents' cataloguing in modern electronic environment is automatic indexing. That kind of indexing considers developed system of metadatas in which some electronic documents are described. The concept of information resource with a help of metadata exists for many years, Nevertheless, nowadays it is very important to develop better system of documents' cataloguing especially for those documents that exist only as a computer form. Therefore the role of metadata in describing the information net resources is of great importance for future knowledge bases.
Projekt MZOS
HRV